Estimating transboundary economic damages from climate change and air pollution for subnational incentives for green on-road freight. (May 2020) - Wang, Wilson; Saari, Rebecca K.; Bachmann, Chris; Mukherjee, Ushnik
Highlights: Freight trucking emits substantial amounts of air pollutants and greenhouse gases. These emissions yield multibillion dollar annual economic damages in Ontario. Damages imply an economic incentive level that could inform policy development. Modest zero-emission vehicle adoption can meet relevant emission reduction targets. Abstract: Subnational incentives to adopt zero emission vehicles (ZEVs) are critical for reducing the external economic damages posed by transportation to air quality and the climate. Few studies estimate these damages for on-road freight, especially at scales relevant for subnational policies requiring cross-border cooperation. Here, we assess the damages to US receptors from emissions of air pollutants (PM2.5, NOx, SO2, NH3 ), and greenhouse gases (CO2, CH4, N2 O) from medium and heavy duty freight trucking, and the benefits of ZEV adoption by census division in the Province of Ontario. We develop an integrated modelling framework connecting a travel demand model, a mobile emissions simulator, and a regression based marginal damages model of air pollutants and climate change. We estimate $1.9 billion (2010 USD) in annual cross-border damages, or $0.16/VKT, resulting from scaled up atmospheric emissions from a 'typical day' of medium and heavy duty truck traffic volume for Ontario in 2012. This implies approximately $8000 per truck per year in damages, which could inform an economic incentive for emission reduction. The provincial goal of 5% ZEV adoption would reduce GHG emissions in 2012 by 800 ktCO2 e, yielding $89 Million (2010 USD) in cross-border benefits annually, with air quality co-benefits of $83/tCO2 e. This result varies between −19% and 22% based on sensitivity analysis for travel and emissions models, though economic damages are likely the largest uncertainty source. Such advances in subnational scale integrated modeling of the environmental impacts of freight can offer insights into the sustainable design of clean freight policy and programs.